Analisis Postur Tubuh Pada Pekerjaan Manual Handling Menggunakan Metode Owas (Ovako Working Analysis System) Pada Pekerja di Pt. Xyz - Amalia, Ridha; Parji, Parji; Lukman, M. (Syntax Literate, 2025)
This study aims to examine the results of postural assessment during manual handling tasks performed by workers at PT Pertamina RU V Terminal Lawe-Lawe. The research employs the Nordic Body Map (NBM) questionnaire to identify and measure the prevalence of musculoskeletal complaints, particularly lower back pain and muscle discomfort as reported by the workers. Data collection was conducted through the distribution of questionnaires and structured interviews. The analysis of working postures was carried out using the Ovako Working Posture Analysis System (OWAS), a method designed to evaluate and categorize postural risks in the workplace. The assessment focused on three main stages of manual handling activities: (1) lifting the electrical panel, (2) transporting the electrical panel, and (3) placing the panel back down. These activities involved two workers conducting the manual handling tasks. The results indicated that the postures adopted during these tasks fell into Category 3 of the OWAS classification, which signifies a high level of risk and the need for immediate corrective measures. Based on the findings, several ergonomic interventions are recommended, including the use of appropriate ergonomic assistive devices according to the work environment, performing muscle stretching exercises prior to manual handling, and conducting regular health screenings to monitor musculoskeletal health.